Myelin Debris Stimulates NG2/CSPG4 Expression in Bone Marrow-Derived Macrophages in the Injured Spinal Cord - Liu, Yang; Hammel, Grace; Shi, Minjun; Cheng, Zhijian; Zivkovic, Sandra; Wang, Xiaoqi; Xu, Pingyi; He, Xijing; Guo, Bing; Ren, Yi; Zuo, Li (Frontiers in Cellular Neuroscience, 2021)
Although the increased expression of members of the chondroitin sulfate proteoglycan family, such as neuron-glial antigen 2 (NG2), have been well documented after an injury to the spinal cord, a complete picture as to the cellular origins and function of this NG2 expression has yet to be made. Using a spinal cord injury (SCI) mouse model, we describe that some infiltrated bone marrow-derived macrophages (BMDMΦ) are early contributors to NG2/CSPG4 expression and secretion after SCI. We demonstrate for the first time that a lesion-related form of cellular debris generated from damaged myelin sheaths can increase NG2/CSPG4 expression in BMDMΦ, which then exhibit enhanced proliferation and decreased phagocytic capacity. These results suggest that BMDMΦ may play a much more nuanced role in secondary spinal cord injury than previously thought, including acting as early contributors to the NG2 component of the glial scar.